Cancer‐related financial hardship among head and neck cancer survivors: Risk factors and associations with health‐related quality of life. Issue 4 (7th March 2019) - Lu, Liya; O'Sullivan, Eleanor; Sharp, Linda
Abstract: Objective: Cancer survivors are susceptible to financial hardship. In head and neck cancer (HNC) survivors, we investigated (a) predictors for cancer‐related financial hardship and (b) associations between financial hardship and health‐related quality of life (HRQoL). Methods: We conducted a cross‐sectional study in HNC survivors identified from the National Cancer Registry Ireland. HRQoL was based on the Functional Assessment for Cancer Therapy General (FACT‐G) plus Head and Neck Module (FACT‐HN). Objective cancer‐related financial hardship (financial stress) was assessed as household ability to make ends meet due to cancer and subjective financial hardship (financial strain) as feelings about household financial situation due to cancer. Modified Poisson regression was used to identify predictors for financial hardship. Bootstrap linear regression was used to estimate associations between hardship and FACT domain scores. Results: Pre‐diagnosis retirement (relative risk [RR] 0.50, 95% confidence interval [CI] 0.37‐0.67), pre‐diagnosis financial stress (RR 1.85, 95% CI 1.58‐2.15), and treatment were significantly associated with objective financial hardship. Predictors of subjective financial hardship were similar: aged greater than or equal to 65 years, pre‐diagnosis financial stress, and treatment. Participants with objective financial hardship reported significantly lower physical (coefficient −3.45, 95% CI −4.39 to −2.44), emotional (−2.01, 95% CI −2.83 to −1.24), functional (−2.56, 95% CI −3.77 to −1.33) and HN‐specific HRQoL (−3.55, 95% CI −5.04 to −2.23). Physical, emotional, and functional HN‐specific HRQoL were also significantly lower in participants with subjective financial hardship. Conclusion: Cancer‐related financial hardship is common and associated with worse HRQoL among HNC survivors. This supports the need for services and supports to address financial concerns among HNC survivors.